Front Cover: Thermal and Gas Adsorption Properties of Tröger's Base/Diaza‐cyclooctane Hybrid Ladder Polymers (ChemNanoMat 7/2021). Issue 7 (15th June 2021) - Inoue, Keiki; Selyanchyn, Roman; Fujikawa, Shigenori; Ishiwari, Fumitaka; Fukushima, Takanori
Abstract : Hybrid ladder polymers containing Tröger's base (TB) and diazacyclooctane (DACO) units in the main chain with various contents of DACO unit were systematically synthesized by sequential post‐polymerization modification including N ‐methylation and alkaline hydrolysis of TB‐based ladder polymers to investigate the effect of DACO content on the thermal and gas adsorption properties of the hybrid ladder polymers. Notably, the presence of DACO unit improves the adsorption selectivity of CO2 against N2 compared with an original TB‐based ladder polymer, while the TB/DACO hybrid ladder polymers partly maintain their intrinsic microporosity. More information can be found in the Full Paper by Fumitaka Ishiwari, Takanori Fukushima et al.